Primordial non-Gaussianity without tails – how to measure fNL with the bulk of the density PDF. Issue 1 (6th August 2020) - Friedrich, Oliver; Uhlemann, Cora; Villaescusa-Navarro, Francisco; Baldauf, Tobias; Manera, Marc; Nishimichi, Takahiro
ABSTRACT: We investigate the possibility to detect primordial non-Gaussianity by analysing the bulk of the probability distribution function (PDF) of late-time cosmic density fluctuations. For this purpose, we devise a new method to predict the impact of general non-Gaussian initial conditions on the late-time density PDF. At redshift z = 1 and for a smoothing scale of 30 Mpc h −1 our predictions agree with the high-resolution Quijote N -body simulations to 0.2 per cent precision. This is within cosmic variance of a ∼100(Gpc h −1 ) 3 survey volume. When restricting to this 30 Mpc h −1 smoothing scale and to mildly non-linear densities (δ[30 Mpc h −1 ] ∈ [−0.3, 0.4]) and also marginalizing over potential ignorance of the amplitude of the non-linear power spectrum an analysis of the PDF for such a survey volume can still measure the amplitude of different primordial bispectrum shapes to an accuracy of Δ f_NL^loc = ± 7.4 Δ f_NL^equi = ± 22.0 Δ f_NL^ortho = ± 46.0 . When pushing to smaller scales and assuming a joint analysis of the PDF with smoothing radii of 30 and 15 Mpc h −1 (δ[15 Mpc h −1 ] ∈ [−0.4, 0.5]) this improves to Δ f_NL^loc = ± 3.3 Δ f_NL^equi = ± 11.0 Δ f_NL^ortho = ± 17.0 – even when marginalizing over the non-linear variances at both scales as two free parameters. Especially, such an analysis could simultaneously measure f NL and the amplitude and slope of the non-linear power spectrum. However, at 15 Mpc h −1 our predictions are only accurate to 0.8 per cent for the considered density range. We discuss how this has to be improved in order to push to these small scales and make full use of upcoming surveys with a PDF-based analysis.